High Risk Perception Of The Infected Sexually Transmitted Infections (Sti) Sti Clinic On In Padang Bulan Public Health Centers Medan City In 2014 - Mutia, Ayu Febrini (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Clinical STI (Sexually Transmitted Infections) is a prevention program of the government which aSTIâs to carry out the functions of control and reduce the spread of STIs in sex workers, homosexuals, Transgenders, Customers sex workers, and sexual partner fixed. STIâS showed an increasing prevalence. STIâS is an indicator for the entrance of HIV AIDS. STI prevalence from year to year but the increasing attention to STIâS at this time if neglected.This study is a qualitative study that illustrates the perception of a high risk group for contracting STIs clinic utilization of primary STIâS.Data obtained by using indepth interviews and secondary data obtained from the health center as well as the data - other supporting data. Data processing is done by qualitative descriptive method.The results showed the informant to obtain information about STIs Clinic obtained from field officer or Governmental Organization. Their knowledge of STIs clinic is only limited to the examination of HIV / AIDS alone. The whole informants from the high risk group of contracting STDs that sex workers did not know the type - the type of STIs other than HIV / AIDS. Perception of high risk of contracting STIs group formed by the information that they can, they have the knowledge and experience they feel.STI clinics are expected to further maximize the dissemination of information on STI disease in detail and accurately. Expected to support cross-sectoral, especially government in an effort to increase the utilization of STI clinic